Syntheses, Characterization, DFT and Molecular Docking of N-(4-chlorophenyl)-1-(4-nitrophenyl) methanimine, (4-chlorophenyl)-1-(4-methoxyphenyl) methanimine and its derivatives - A. Tawfiq, Asya; J. Mahdi, Omar; H. Hattab, Ahmed (Al-Nahrain Journal of Science, 2026)
The synthesis of numerous chemical compounds relies on imines as a key building ingredient. Several Schiff bases were generated via the acid-catalyzed condensation of aromatic aldehyde derivatives with aniline derivatives. FT-IR, 1HNMR, spectra allowed to identify the products. The ORCA software package was used to obtain the outcome of the Density Functional Theory (DFT) and to comprehend how para substituting impacts the electronic structure of the synthesized compounds. Finally, docking simulation was performed using the Autodock application. At the binding site, the prepared compounds were docked with the 3FYV enzyme.